Comprehensive metabolic and transcriptomic profiling of various tissues provide insights for saponin biosynthesis in the medicinally important Asparagus racemosus - Srivastava, Prabhakar Lal; Shukla, Anurag; Kalunke, Raviraj M. (Scientific reports, 2018)
Asparagus racemosus (Shatavari), belongs to the family Asparagaceae and is known as a “curer of hundred diseases” since ancient time. This plant has been exploited as a food supplement to enhance immune system and regarded as a highly valued medicinal plant in Ayurvedic medicine system for the treatment of various ailments such as gastric ulcers, dyspepsia, cardiovascular diseases, neurodegenerative diseases, cancer, as a galactogogue and against several other diseases. In depth metabolic fingerprinting of various parts of the plant led to the identification of 13 monoterpenoids exclusively present in roots. LC-MS profiling led to the identification of a significant number of steroidal saponins (33). However, we have also identified 16 triterpene saponins for the first time in A. racemosus . In order to understand the molecular basis of biosynthesis of major components, transcriptome sequencing from three different tissues (root, leaf and fruit) was carried out. Functional annotation of A. racemosus transcriptome resulted in the identification of 153 transcripts involved in steroidal saponin biosynthesis, 45 transcripts in triterpene saponin biosynthesis, 44 transcripts in monoterpenoid biosynthesis and 79 transcripts in flavonoid biosynthesis. These findings will pave the way for better understanding of the molecular basis of steroidal saponin, triterpene saponin, monoterpenoids and flavonoid biosynthesis in A. racemosus .